A Note on Spatial Dialectics. (3rd May 2016) - Kobialka, Michal
Abstract : In the notes to the 2015 Venice Biennale, called "All the World's Futures, " Okwui Enwezor's make the following observation: "the global landscape lies shattered and in disarray, scarred by violent turmoil, panicked by specters of economic crisis and viral pandemonium, secessionist politics and a humanitarian catastrophe on the high seas, desserts and borderlands, as immigrants, refugees and desperate people seek refuge in seemingly calmer and prosperous lands." How can the current disquiet—the radical changes from industrial to post-industrial modernity; technological to digital modernity; mass migration to mass mobility, environmental disasters and genocidal conflicts—be grasped and articulated? This essay examines some critical expressions that could be a response to Enwezor's poigniant question. To substantiate this statement, I discuss Herbert Marcuse's 1960 essay "A Note on Dialectic" as well as Henri Lefebvre's notion of spatial dialectics. Unlike dialectics based on an analysis of historical time and of temporality (Hegel and Marx), spatial dialectics focuses on the contradictions which imply and explain contradictions in historical time without being reducible to them. In other words, the notion of contradiction is not restricted to temporality or historicity but draws attention to contradictions and conflicts in space as well as to contradictions of space, reminiscent of the classical contradictions engendered by history and historical time. I will elaborate on this point by bringing the discussion back to the visual and performance art—to Tadeusz Kantor's statements about his use of objects in the 1944 production of The Return of Odysseus and to Abraham Cruzvillegas' autoconstrucción . Both of these artists, I wish to argue, offer a practice which breaks the syntax of the current new materialist turn and of the processes that aestheticize reality, in order to historicize the performative in the age of globalization along the lines of Marcuse's dialectics and Lefebvre's spatial dialectics.